2017
DOI: 10.1136/bmjopen-2016-014815
|View full text |Cite
|
Sign up to set email alerts
|

Has the NHS 111 urgent care telephone service been a success? Case study and secondary data analysis in England

Abstract: ObjectivesTo explore the success of the introduction of the National Health Service (NHS) 111 urgent care service and describe service activity in the period 2014–2016.DesignComparative mixed method case study of five NHS 111 service providers and analysis of national level routine data on activity and service use.Settings and dataOur primary research involved five NHS 111 sites in England. We conducted 356 hours of non-participant observation in NHS 111 call centres and the urgent care centres and, linked to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 5 publications
(5 reference statements)
2
51
0
Order By: Relevance
“…The number of calls where the recommendation was to attend ED was determined. This formed 8% of the total calls triaged (NHS 111, MDS) 6. From this group, calls with recommendation to attend ED either in 1 or 4 hours were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…The number of calls where the recommendation was to attend ED was determined. This formed 8% of the total calls triaged (NHS 111, MDS) 6. From this group, calls with recommendation to attend ED either in 1 or 4 hours were extracted.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, the National Health Service (NHS), the national, free‐at‐the‐point‐of‐entry healthcare system, provides access to advice from healthcare professionals via its 111 telephone call service. Time‐stamped electronic data collected during these calls are used to compare nurse response times and numbers of enquiries resolved within the time required by their protocol (Pope et al, ; Prichard, Turnbull, Halford, & Pope, ; Ruston, ). Previous research has shown that nurses can resist electronically based protocol implementation in overt and covert ways (Pope et al, ; Prichard et al, ; Ruston, ; Timmons, ), thereby undermining the aims of the protocol (Timmermans & Berg, ).…”
Section: Introductionmentioning
confidence: 99%
“…Time‐stamped electronic data collected during these calls are used to compare nurse response times and numbers of enquiries resolved within the time required by their protocol (Pope et al, ; Prichard, Turnbull, Halford, & Pope, ; Ruston, ). Previous research has shown that nurses can resist electronically based protocol implementation in overt and covert ways (Pope et al, ; Prichard et al, ; Ruston, ; Timmons, ), thereby undermining the aims of the protocol (Timmermans & Berg, ). The research to date has focused on NHS 111 (Pope et al, ; Prichard et al, ; Ruston, ) electronic patient records (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retrospective evaluations,2 before and after studies,3 and case study analyses4 are no substitute for randomised controlled trials.…”
mentioning
confidence: 99%